DEPRESSÃO PÓS-PARTO E DESENVOLVIMENTO INFANTIL NOS TRÊS PRIMEIROS ANOS DE VIDA - AZZI, DANIELE (2018)
The increase in health care programs and actions around health education have become a priority and pre-gestation, childbirth and postpartum care are fundamental to a woman's better living conditions. This care is important to the mother, but also to the full development of the infant. The objective of this study is to compare the development of babies with indicators of postpartum depression in mothers, to evaluate indicators of postpartum depression in mothers of infants up to 42 months, to evaluate child development, cognitive aspects, receptive language, expressive language, fine motor, gross motor, social emotional and adaptive behavior of infants up to 42 months, correlate delays in infant development and mother's educational level, correlate delays in child development and family income; correlate delays in child development and help to care for the baby.A hundred mothers and a hundred infants from both sex took part of this study, where the infants were up to 42 months and were matriculated on baby nurseries located in São Bernardo do Campo.The tools used to gather the data were: Sociodemographic Questionnaire, the Edinburgh Postpartum Depression Scale answered by the mothersand the Bayley III Child Development Scale applied to infants. The data was collected individually on each baby nursery and analysed through the statistical software SPSS – Statistical Package for the Social Sciences Version 21. The correlated variables were the following: Mother's depression and delay on infant development, mother’s degree of schooling, fixed income from the family and if the mother have had any help taking care of the infant.The results did not show any direct relation between them, except for the infant development and the fixed income from the family.The research pointed a significant statistical influence from the family's fixed incoming over the infant development. The results show that a low family fixed income might represent a risk factor for when it comes to the development of the infant.